SUMANG: Norm of Gayo Community Within The Framework of Islamic Education - Zulkarnain Zulkarnain; Ardian Al Hidaya; Eliyyil Akbar (AL-TAHRIR, 2019)
Abstract: The rise of immodesty among the young people towards the elderly implies the lack of cultural identity. This behavior is not only performed by individuals within the family environment but also the entire aspects of the educational environment and society. Dealing with this condition, it is necessary to re-actualize the social norms as local wisdom for future generations like Gayo community. Here are the norms to avoid violating actions. These rules are used as a foundation of life called Sumang. This paper focuses on the concepts of Gayo community norms within the framework of Islamic education. This research employed a descriptive qualitative using field research method. The sampling technique was purposive sampling by selecting the research participants consisting of the prominent tribal leader of Gayonese people. The data were collected by using observation and semi-structured interview. Then, the data were documented and analyzed through data reduction, display, and conclusion. The purpose of this paper is to explore the heritage value of Gayo community that can be used as a reference to respond to the challenges of future generations. The findings showed that the Gayo norms managing social interaction known as Sumang (taboo) consisting of Sumang Kenunulen (sitting), Sumang perceraken (talking), Sumang pelangkahan (journey), Sumang penengonen (seeing). Those concepts in Gayo community norms within the framework of Islamic education are to prevent a contradiction to the religion and the cultural values or it can be classified as disrespectful attitudes. These norms have also been the foundation for developing character education.الملخص: يتزايد انتشار الخلافة بين الصغار والكبار بشكل متزايد ، مما يعني نقصًا في الأخلاق. هذا السلوك لا يتم فقط من قبل الأفراد في محيط الأسرة ولكن في جميع جوانب البيئة التعليمية وحتى المجتمع. لمعالجة هذا ، من الضروري الحفاظ على جدول الأعمال أو إعادة تفعيل المعايير الاجتماعية التي أصبحت حكمة محلية لأجيال. كما هو الحال في مجتمع Gayo ، لديها قواعد السلوك أو السلوك التي يجب تجنبها لخرق القيم. تستخدم القاعدة كنمط أساسي أو أساس للحياة يسمى سومانغ. تستعرض هذه الورقة معايير مجتمع Gayo ومفاهيم معايير مجتمع Gayo في إطار التعليم الإسلامي. تستخدم طريقة البحث هذه النوعية الوصفية ، مع البحث الميداني. استخدم المشاركون في هذه الورقة تقنية أخذ عينات هادفة ، وهي الشكل التقليدي لمجتمع جايو. طرق جمع ملاحظات البيانات ، ومقابلات الفصول ، والتوثيق أثناء تحليل البيانات باستخدام تقليل البيانات ، وعرض البيانات والاستنتاجات .الغرض من هذه الورقة هو استكشاف القيمة التراثية لمجتمع غايو ويمكن استخدامه كمرجع في الرد على تحديات الأجيال التي تفتقر إلى الأخلاق. تشير النتائج في هذا المجال إلى أن قواعد جايو التي تحكم التفاعل الاجتماعي تُعرف باسم سومانج كينونولن (المتنافرة عند الجلوس) ، ووسانجانج بيرسيكاكن (المتناقض في قول الكلمات) ، والسومانج بيلانجكان (المتناقض في السفر) ، وسومانج بيننغونين (طرق متضاربة للرؤية) ، إن مفهوم معايير مجتمع جايو في إطار التربية الإسلامية هو فعل يتعارض مع الدين ، لأنه يصنف كموقف غير جدير بالثناء وله تأثير غير موات ، ويمكن أن يكون هذا الأساس أساسًا لقيم الشخصية المتنامية.Abstrak: Maraknya sikap ketidaksopanan antara yang muda terhadap yang tua semakin merambah sehingga mensiratkan minimnya etika. Tingkah laku tersebut bukan hanya dilakukan individu di lingkungan keluarga, namun pada seluruh aspek lingkungan pendidikan bahkan masyarakat. Untuk menyikapi hal tersebut, perlu agenda pelestarian atau mengaktualisasikan kembali norma-norma sosial yang sudah menjadi kebijaksaan lokal secara turun temurun. Sebagaimana pada masyarakat Gayo, mempunyai aturan perbuatan atau tingkah laku yang harus dijauhi karena melanggar nilai. Aturan tersebut dijadikan pola dasar atau landasan hidup yang disebut Sumang. Tujuan tulisan ini untuk menggali nilai pusaka masyarakat Gayo dan dapat dijadikan acuan dalam menjawab tantangan generasi yang minim moralitas. Metode penelitian ini menggunakan deskriptif kualitatif, dengan penelitian lapangan (field research) serta partisipan menggunakan teknik purposive sampling,yaitu tokoh adat masyarakat Gayo. Pengumpulan data menggunakan pengamatan, wawancara semiterstruktur, dokumentasi, sedangkan analisa data menggunakan data reduction, displaydata serta kesimpulan. Temuan di lapangan bahwa norma masyarakat Gayo yang mengatur tata pergaulan dalam berinteraksi dikenal dengan istilah sumang kenunulen (sumbang ketika duduk), sumang perceraken (sumbang dalam mengucapkan kata-kata), sumang pelangkahen (sumbang dalam perjalanan), sumang penengonen (sumbang cara melihat). Konsep norma-norma masyarakat Gayo dalam bingkai pendidikan Islam merupakan tindakan yang bertentangan dengan adat, agama karena tergolong sikap yang tidak terpuji dan berdampak tidak baik. Norma tersebut juga telah menjadi dasar untuk menumbuhkan nilai-nilai karakter.